The Effect of Grinding Media on Mineral Breakage Properties of Magnetite Ores - Liang Si; Yijun Cao; Guixia Fan (Geofluids)
The breakage and liberation of minerals are the key to fluidized mining for minerals. In the ball milling process, steel balls function as not only a grinding action implementer but also energy carrier to determine the breakage behavior of ores and the production capacity of the mill. When ground products present a much coarse or much fine particle size distribution, the separation process will suffer, resulting in inefficient recovery of useful minerals. Optimal control of the particle size distribution of the products is therefore essential, but the complexity and randomness of ball mill grinding make it difficult to determine the appropriate ball size. To solve the problem in the precise measurement of grinding ball diameters, this paper carried out magnetite grinding experiments with grinding balls of different diameters under the same grinding conditions to study the influence pattern of steel ball diameters on the particle break behavior, the particle size distribution of ground products, and the mineral liberation degree distribution. The research proposed on the matching relation between the ball size and the quality of ground products is essential for improving the ground product quality and reducing energy consumption.